Molecular profiling of clinical remission in psoriatic arthritis reveals dysregulation of FOS and CCDC50 genes: a gene expression study - Maria Maddalena Angioni; Maria Maddalena Angioni; Alberto Floris; Alberto Floris; Ignazio Cangemi; Mattia Congia; Mattia Congia; Elisabetta Chessa; Elisabetta Chessa; Micaela Rita Naitza; Matteo Piga; Matteo Piga; et al. (Frontiers in Immunology, 2023)
BackgroundIn psoriatic arthritis (PsA), the primary goal of treatment is clinical remission. This study aimed to characterize the molecular profile underlying the induced clinical remission in patients with PsA, comparing the remission state and the healthy condition.MethodsWhole blood transcriptomic analysis was performed on groups of 14 PsA patients in TNFi-induced clinical remission (DAPSA ≤ 4), 14 PsA patients with active disease (DAPSA > 14), and 14 healthy controls (HCs). Then, all differentially expressed genes (DEGs) derived from remission vs. HC comparison were analyzed for functional and biological characteristics by bioinformatics software. The gene expression of 12 genes was then validated by RT-qPCR in an extended cohort of 39 patients in clinical remission, 40 with active disease, and 40 HCs.ResultsThe transcriptomic analysis of PsA remission vs. HCs highlighted the presence of 125 DEGs, and out of these genes, 24 were coding genes and showed a great involvement in immune system processes and a functional network with significant interactions. The RT-qPCR validation confirming the down- and upregulation of FOS (FC −2.0; p 0.005) and CCDC50 (FC +1.5; p 0.005) genes, respectively, in line with their role in orchestrating inflammation and bone metabolism processes, may be related to PsA pathophysiology.ConclusionThe transcriptomic profile of clinical remission in PsA is similar to a healthy condition, but not identical, differing for the expression of FOS and CCDC50 genes, which appears to play a key role in its achievement.